Mom the Chemistry Professor Personal Accounts and Advice from Chemistry Professors who are Mothers - Woznack, Kimberly; Charlebois, Amber; Cole, Renée; Marzabadi, Cecilia; Webster, Gail.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
When is the "right" time? How can I meet the demands of a professorship whilst caring for a young family? Choosing to become a mother has a profound effect on the career path of women holding academic positions, especially in the physical sciences. Yet many women successfully manage to do both. In this second edition, which is a project of the Women Chemists Committee (WCC) of the American Chemical Society (ACS), 40 inspirational personal accounts describe the challenges and rewards of combining motherhood with an academic career in chemistry. The authors are all women at different stages of their career and from a range of institution types, in both tenure and non-tenure track positions. The authors include women from different racial and ethnic backgrounds, who became mothers at different stages of their career, and who have a variety of family structures. Aimed at undergraduate and graduate students of chemistry, as well as postdoctoral fellows and early career faculty, these contributions serve as examples for women considering a career in academia but worry about how this can be balanced with other important aspects of life. The authors describe how they overcame particular challenges, but also highlight aspects of the system, which could be improved to accommodate women academics, and particularly encourage more women to take on academic positions in the sciences.
Introduction -- Safety Chapter -- The Best Job in the World -- Equilibrium and Stress: Balancing One Marriage, a "Two-Body Problem," and Three Children -- If at First You Don't Succeed, Don't Give Up on Your Dreams -- Invictus -- My Circus: Please Note That I Have No Formal Training in Juggling -- Planned Serendipity -- Readymade Family -- Mother and Community College Professor -- From Pre-med to U.S. Professor of the Year: My Personal Journey -- Minha Vida e Minha Carreira e Minha Família (My Life and My Career and My Family) -- Chemistry in the Family -- Are You Always This Enthusiastic? -- How Motherhood Shaped My Professorship -- Upward Bound to a Ph.D. in Chemistry -- I'm.a.Gene- Destined for a Career in the Sciences -- It Always Seems Impossible Until It Is Done -- On Breastfeeding, Supramolecular Chemistry, and Long Commutes: Life as an Assistant Professor, Wife, and Busy Mother of Three -- TheWindow of Opportunity -- Pieces of a Puzzle -- Wanting It All -- On Our Own Terms -- Family First, Extraordinary Career -- Family Matters: How Family Influenced my Career -- Mother and Chemist: Every pitfall is an opportunity to rise with a new beginning -- Taking an Unconventional Route? -- The path to academia and motherhood: It takes a village -- Elements to Successful Motherhood and the Professoriate -- A Family Grows -- Teacher to Scientist and Back Again -- A Divinely Ordered Path -- Raising three children across three continents -- Ebony and Women and Science....... Oh My! -- From the Periodic Table to the Dinner Table -- The Bigger Picture: My Journey to a Purposeful Life and Career in Academia -- Encounters of the Positive Kind -- The Long and Winding Road -- I Finally Know What I Want to Be When I Grow Up -- Finding Rhythm -- My Not-So-Secret Double-Life as a Chemistry Professor and Mom -- Remarkable, Delightful, Awesome: It Will Change Your Life, Not Overnight but Over Time.
Keywords: Chemistry; Technology -- Sociological aspects; Sex; Chemistry; Science, Technology and Society; Gender Studies